A comparative investigation of thermodynamic performance and flow field structure of a modified Collins cycle-based helium turboexpander system. (October 2021) - Kumar, Manoj
Abstract: The optimum design of radial expansion turbine and nozzle (turboexpander) have a remarkable effect on the thermophysical performance of gas liquefaction cycles. The present study proposes a new mean-line design, sensitivity analysis, and optimization method to develop three turboexpander systems for a modified Collins cycle-based helium liquefaction system. The proposed method deals with the real gas equation of state to determine the turboexpander configurations and their performance at off-design conditions. The mean-line design approach integrated with different loss correlations has been performed using an in-house code in Matlab® environment. Furthermore, sensitivity analysis and artificial neural network-based optimization process of thirteen design coefficients and non-dimensional variables has been carried out which improves the off-design performance of the turboexpander up to 4.43%, 12.57%, and 16.36% for total-to-static efficiency, total losses, and power output respectively. Applying the aforementioned procedure, three turboexpanders have been designed. After that, a three-dimensional transient blade-row turbulent flow simulations have been carried out to stimulate the rotor-stator interaction at different operating conditions (25 bar & 80 K, 7 bar & 50 K, and 25 bar & 30 K) and rotational speeds (2.84 × 10 5, 1.61 × 10 5, and 2.75 × 10 5 rpm) using k-ω shear stress transport turbulence model. The commercial Navier-Stokes finite volume solver ANSYS CFX® has been used to study a comparative thermodynamic performance and flow field structures at different streamwise and spanwise directions of the entire flow passage. Additionally, the present numerical results have been validated with available experimental and computational data in the open literature. The present design, optimization, and numerical procedure presented herein will be advantageous for the future development of efficient small-scale turboexpander systems subjected to wide operating ranges.